A descriptive study of step alignment and foot positioning relative to the tee by professional rugby union goal-kickers - Cockcroft, J.; Van Den Heever, D. (Journal of Sports Sciences, 2016)
This study describes foot positioning during the final two steps of the approach to the ball amongst professional rugby goal-kickers. A 3D optical motion capture system was used to test 15 goal-kickers performing 10 goal-kicks. The distance and direction of each step, as well as individual foot contact positions relative to the tee, were measured. The intra- and inter-subject variability was calculated as well as the correlation (Pearson) between the measurements and participant anthropometrics. Inter-subject variability for the final foot position was lowest (placed 0.03 ± 0.07 m behind and 0.33 ± 0.03 m lateral to the tee) and highest for the penultimate step distance (0.666 ± 0.149 m), performed at an angle of 36.1 ± 8.5° external to the final step. The final step length was 1.523 ± 0.124 m, executed at an external angle of 35.5 ± 7.4° to the target line. The intra-subject variability was very low; distances and angles for the 10 kicks varied per participant by 1.6-3.1 cm and 0.7-1.6°, respectively. The results show that even though the participants had variability in their run-up to the tee, final foot position next to the tee was very similar and consistent. Furthermore, the inter- and intra-subject variability could not be attributed to differences in anthropometry. These findings may be useful as normative reference data for coaching, although further work is required to understand the role of other factors such as approach speed and body alignment.